Evaluating the effect of nutritional support in geriatric inpatients classified by the GLIM criteria - Shan Jiang; Xiling Chen; Lan Ma; Qihao Guo; Lan Luo; Yuehui Wang; Xuan Qu; Jiaojiao Li; Liping An; Wei Huang; Yonghua Wu; Hongyu Zhang; et al. (The Journal of Nutrition, Health and Aging)
Objectives: In this study, we aimed to explore the impact of nutrition therapy on clinical outcomes for patients classified according to the Global Leadership Initiative on Malnutrition (GLIM) criteria. Design: Prospective, multicenter cohort study. Setting: This study was conducted from September 2020 to December 2022 across 28 geriatric centers in China. Participants: A total of 862 patients aged ≥65 years were included. Intervention: All participating physicians completed a 6-h training on nutritional support, following international guidelines before the study. Patients had a nutritional risk screening 2002 score ≥3 points within 48 h of admission. Physicians determined specific nutritional support regimens. Measurements: GLIM assessments were conducted after enrollment. Nutritional and functional statuses were evaluated at baseline and 90 days after admission. Clinical outcomes—mortality, readmission, new infections, and falls—were documented after 90 days. Results: Compared to 108 patients without malnutrition per the GLIM criteria, 754 malnourished patients showed lower weight, body mass index (BMI), and Mini Nutritional Assessment-Short Form (MNA-SF) scores and significant reductions in grip strength, calf circumference, and Barthel activities of daily living (ADLs) index. The percentage of patients with adequate caloric intake at the 90-day follow-up was 70.7% (n = 533) and 67.6% (n = 73) in the malnutrition and non-malnutrition groups (p = 0.51) and that of patients with adequate protein intake was 65.9% (n = 497) and 58.3% (n = 63), respectively (p = 0.12). Moreover, malnourished patients showed significant improvements in body weight, BMI, MNA-SF scores, calf circumference, and Barthel ADL index compared to those without malnutrition. Malnourished patients also had lower risks of readmission and falls at follow-up. Conclusion: Among older inpatients at nutritional risk, those with malnutrition classified according to the GLIM criteria benefited from nutritional support, demonstrating improved BMI, MNA-SF scores, calf circumference, and Barthel ADL index, as well as reduced readmission rates and incidence of falls.